La hipoterapia y su incidencia en la rehabilitación de la espasticidad muscular de los niños, niñas y jóvenes con problemas de discapacidad que asisten al “Centro de Hipoterapia Senderos de Alegria” de la ciudad de Loja, durante el año 2012 - Vicente Mera, Xiomara Gabriela (2015)
This research refers to "hippotherapy AND ITS IMPACT ON THE REHABILITATION OF MUSCULAR SPASTICITY children and youth with disabilities attending the" center hippotherapy PATH Joy "from the city of Loja, DURING THE YEAR 2012”. In the present investigation the general objective raised was: Conduct a study of the incidence of hippotherapy in the rehabilitation of children and youth with muscular spasticity attending the rehab trail Joy of Loja.The methods used in the preparation of this research work were: Scientific, inductive deductive, analytic and descriptive Synthetic; that allowed for discussion and comparison of the proposed variables. The instruments used were: asurvey center for two therapists; and motor development scale applied to children and youth. The total population of 80 children and 8 therapists, the shows are 10 children and young people, with the view shows the diagnosis of muscular spasticity that rests on the center and two therapists, who work in the area of hippotherapy. As a result of the investigation, it was concluded that 100% of hipoterapeuticas therapists use only two positions: lying face down and sitting normally, and that the level of gross motor development of most children and young people is of 5-7 years level that differs significantly from your chronological age, showing delays of up to seven years.The center therapists recommend the use of various therapeutic positions hiccups posed by hypo-therapeutic approach, considering the condition of each child or young person and the objective pursued by the treatment.